Waning immunity 14 months after SARS-CoV-2 infection - Stich, Maximilian; Benning, Louise; Speer, Claudius; Garbade, Sven; Bartenschlager, Marie; Kim, Heeyoung; Gleich, Florian; Jeltsch, Kathrin; Haase, Bettina; Janda, Ales̆; Renk, Hanna; Elling, Roland; et al. (Pediatrics, 2022)
Long-term data on the humoral immune response and cross-neutralization against variants of concern in children >1 year after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are currently missing and urgently needed to predict the likelihood of reinfections and guide vaccination strategies.
Accepted: August 02 2022
Gesehen am 27.03.2023